PERBANDINGAN DAYA TERIMA MAKANAN SERTA FAKTOR-FAKTOR YANG MEMPENGARUHI PADA SISTEM PENYELENGGARAAN MAKANAN SWAKELOLA DAN OUTSOURCING - Ilham Sunarya; Widyana Lakshmi Puspita (Poltekkes Kemenkes Pontianak, 2018)
Power of acceptance is the ability of a person to spend the food served according to his needs. To maintain good health and to perform its functions properly, the human body needs nutrients including the energy needs of food. In an effort to improve the health of patients, attention to the improvement of food and nutrition services by the institution to the patient is a matter to note. This study aims to determine the ratio of food acceptance as well as the factors that affect the system of self-managed food and outsourcing. This research is Quantitative research with cross sectional approach. The population of this study were all 3rd grade patients at RSUD Sultan Syarif Mohamad Alqadri Pontianak and RSUD dr Agoesdjam Ketapang which amounted to 100 people. The data collected in the form of primary data and secondary data. The analysis used is Chi-Square and T-Test. The results showed that both hospitals received food in good category under <20% but in Hospital with better self-managed feeding system, rather than the system of feeding oursourcing is dikarnakan on food outsourcing organizing system is not monitored from manufacture to to distribution. It is suggested that Sultan Syarif Mohamad Alqadri Hospital Pontianak to evaluate food remnants for 3 months regularly and thoroughly in all patients, and in ketapang hospital to add cooking power